OBYEKTIVITAS ILMU SEJARAH DITINJAU DARI AKSIOLOGI ILMU HUGH LACEY - , AULIA DHETIRA HARYADI ([Yogyakarta] : Universitas Gadjah Mada, 2013)
History objectivity Studied from Hugh Lacey science axiology tried to give a view about objectivity concept within history as part as science and how value role in history. History studied about past event which connected with human as part of it. Humans life always tied with values with or within them. Science, for Lacey have to their own values to keep the objectivity of science. There are three problems of the research are : values rules in history objectivity, Laceyâs axiology, and history objectivity studied from Laceyâs axiology. Method of this research are description which tried to explain role of values in history. Interpretation will explain about understanding and argument about history objectivity. The last is heuristic whicih giving new understanding about history objectivity studied from Hugh Lacey axiology. The main results of this research are: understanding about values roles in history objectivity. Laceyâs thesis such as impartiality, neutrality, and otonomy could make subjectivity as base of history objectivity. Objectivity couldnât captured values rules. Reconstructing history fact need subjectivity to be meaning and complete event.